2021
DOI: 10.3390/ijms23010009
|View full text |Cite
|
Sign up to set email alerts
|

HOXC6-Mediated miR-188-5p Expression Induces Cell Migration through the Inhibition of the Tumor Suppressor FOXN2

Abstract: Homeobox C6 (HOXC6) is a transcription factor that plays a role in the malignant progression of various cancers. However, the roles of HOXC6 and its regulatory mechanism remain unclear. In this study, we used microRNA (miRNA) regulatory networks to identify key regulatory interactions responsible for HOXC6-mediated cancer progression. In microarray profiling of miRNAs, the levels of miRNAs such as hsa-miR-188-5p, hsa-miR-8063, and hsa-miR-8064 were significantly increased in HOXC6-overexpressing cells. Higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Contradicting our results, previous studies have shown that FOXN2 may serve as a tumor suppressor in breast cancer [ 10 ], lung cancer [ 11 ], and human oral cancer [ 12 ]. The degradation of FOXN2 promotes tumorigenesis and radioresistance in lung cancer cells [ 11 ], but our results identified FOXN2 as a possible oncogene in PAAD ( Figures 1B , 2B ).…”
Section: Discussionsupporting
confidence: 70%
“…Contradicting our results, previous studies have shown that FOXN2 may serve as a tumor suppressor in breast cancer [ 10 ], lung cancer [ 11 ], and human oral cancer [ 12 ]. The degradation of FOXN2 promotes tumorigenesis and radioresistance in lung cancer cells [ 11 ], but our results identified FOXN2 as a possible oncogene in PAAD ( Figures 1B , 2B ).…”
Section: Discussionsupporting
confidence: 70%
“…S2(f–k). According to the literature, hsa-miR-8063 was found to inhibit pancreatic cancer progression through inducing inhibition on ZFP91 [63], to suppress the epithelial–mesenchymal transition of lung cancer cells by regulating its target gene MAGAT3 [64], and to induce cell migration through inhibition of the tumour suppressor FOXN2 [65]. Hsa-mir-4745–5p was strongly dysregulated in Parkinson’s disease (PD) and can be directly regulated by HNF4a [66], which was identified as a longitudinal PD blood biomarker [67].…”
Section: Resultsmentioning
confidence: 99%
“…Hsa-miR-188-5p is highly expressed in cancer and can be used as a prognostic indicator in HCC [ 26 , 27 ]. Our results showed that hsa-miR-188-5p expression was remarkably elevated in cirrhosis.…”
Section: Discussionmentioning
confidence: 99%